Estudo da prevalência da infecção pelo Papiloma Vírus Humano (HPV) em mulheres no climatério em um hospital de referência de Belém - BALBI, Florentina do Socorro Martins (Universidade Federal do Pará, 2015)
HPV infects a large proportion of women worldwide. Approximately 291 million women worldwide are carriers of this virus. HPV is the cause of cervical cancer, that the incidence is higher in women after 40 years old, the same age of climacteric. Therefore, it is important to investigate the presence of HPV genital infection and risk factors in climacteric women to evaluate cervical cancer susceptibility. This study is to investigate HPV genital infection in climacteric women in Belém city. We evaluated 213 women between 35 and 60 years old, whose are assistance at Ambulatório da Mulher da Fundação Santa Casa do Pará. Clincal and epidemiologic data were collected using a questionnaire. Cervical cells were collected using cytological brush to detect HPV DNA. HPV DNA was detected using PCR with MY9/MY11 primers. To type HPV 6, 11, 16, 18, 31, 33, 35, 52 e 58, it was performed using real time PCR with specific probes. Among 213 women, HPV genital infection was 11,7%. Associated risk factors were irregular use of condom and sexual initiation before 14 years old. Subtypes HPV frequency were 4% to HPV 11, 16, 31, 33 and 8% to HPV 6 e 35.